Sagot :
Answer:
6x² - 6x - 12
Step-by-step explanation:
(2x)(3x) + (-4)(3) + (-4)(3x) + (2x)(3)
6x² -12 - 12x + 6x
= 6x² - 6x - 12
[tex] \large{\sf{Problem}}[/tex]
which of the following shows the Foil method of multiplying (2x-4) and (3x +3)?
[tex] \large{\sf{Solution}}[/tex]
[tex] \large{\tt{(2x - 4) \: (3x + 3)}}[/tex]
[tex] \tt{ = (2x) \: (3x) + \: (2x) \: (3) + \: ( - 4) \: (3x) + \: ( - 4) \: (3)}[/tex]
[tex] \tt{= 6 {x}^{2} + 6x - 12x - 12}[/tex]
[tex] \bold{\tt{= 6{x}^{2} - 6x - 12}}[/tex]
[tex] \large{\sf{Answer}}[/tex]
[tex] \sf{(2x - 4) \: (3x + 3)} \: = \: \boxed{\large{\sf{6 {x}^{2} - 6x - 12}}}[/tex]